Molecular diversity of rice germplasms from Thailand characterized by different pericarp colors using Inter Simple Sequence Repeat (ISSR) markers - JUTHAPORN SAENGPRAJAK; JIRAPA PHETSOM; APHIDECH SANGDEE; PORNTIP ATICHART; PIYADA THEERAKULPISUT (Society for Indonesian Biodiversity, 2024)
Abstract. Saengprajak J, Phetsom J, Sangdee A, Atichart P, Theerakulpisut P. 2024. Molecular diversity of rice germplasms from Thailand characterized by different pericarp colors using Inter Simple Sequence Repeat (ISSR) markers. Biodiversitas 25: 2839-2848. Studying genetic diversity in rice using molecular markers is necessary for varietal identification, better understanding of relationships and evolution, and conserving genetic resources. This study aimed to evaluate the genetic diversity of rice germplasms from Thailand characterized by different pericarp colors using ISSR markers. Thirty-two white and colored rice genotypes were assessed using 16 selected ISSR markers, which generated 179 alleles ranging from 210 to 1,374 bp, averaging 11.19 alleles per locus. The polymorphism percentage ranged from 40% to 100%, averaging 80%. The genetic similarity coefficient ranged from 0.458 to 0.855, while PIC values varied between 0.15 and 0.45, averaging 0.31. ISSR markers show a high Resolving Power (RP) of 12.15 and a Marker Index (MI) of 3.20, indicating their significant discriminatory power and effectiveness in detecting genetic diversity. The dendrogram grouped genotypes into five clusters: Cluster I included 5 red pericarp genotypes, Cluster II had 6 purple-black pericarp genotypes, Cluster III had 2 mixed white and purple-black pericarp genotypes, Cluster IV included 18 white pericarp genotypes, and Cluster V comprised 1 white pericarp genotype. PCA results corresponded to seed coat traits, forming eight grouping patterns similar to dendrogram clusters. These findings show that ISSR markers effectively assess genetic diversity and relationships in rice germplasms, providing valuable information for managing germplasm resources, developing variety-specific markers, and supporting rice breeding programs.